Intimal Hyperplasia and Arteriovenous Fistula Failure: Looking Beyond Size Differences. Issue 8 (26th August 2021) - Vazquez-Padron, Roberto I.; Duque, Juan C.; Tabbara, Marwan; Salman, Loay H.; Martinez, Laisel
Abstract: The development of venous intimal hyperplasia (IH) has been historically associated with failure of arteriovenous fistulas (AVFs) used for hemodialysis. This long-standing assumption, made on the basis of histologic observations, has been recently challenged by clinical studies indicating that the size of the intima by itself is not enough to explain stenosis or AVF maturation failure. Irrespective of this lack of association, IH is present in most native veins and fistulas, is prominent in many patients, and suggests a role in the vein that may not be reflected by its dimensions. Therefore, the contribution of IH to AVF dysfunction remains controversial. Using only clinical data and avoiding extrapolations from animal models, we critically discuss the biologic significance of IH in vein remodeling, vascular access function, and the response of the venous wall to repeated trauma in patients receiving hemodialysis. We address questions and pose new ones such as the following: What are the factors that contribute to IH in preaccess veins and AVFs? Do cellular phenotypes and composition of the intima influence AVF function? Are there protective roles of the venous intima? This review explores these possibilities, with hopes of rekindling a critical discussion about venous IH that goes beyond thickness and AVF outcomes.